2000
DOI: 10.4049/jimmunol.164.4.1746
|View full text |Cite
|
Sign up to set email alerts
|

TCR-Independent Activation of Extrathymically Developed, Self Antigen-Specific T Cells by IL-2/IL-15

Abstract: Naive intrathymically developed T cells, which express foreign Ag-specific TCR, do not express IL-2R. After antigenic stimulation, they express high affinity IL-2R, which enables IL-2 to be used as an autocrine growth factor. On the contrary, extrathymically developed T cells, which express self Ag-specific TCR but are unresponsive to antigenic stimulation, spontaneously express low affinity IL-2R. In this study, we compared the responses of these two subsets of T cells to IL-2R stimulation and examined the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…Previous studies had shown that the expansion of self-specific CD8 T cells in response to either IL-2 or IL-15 in vitro was independent of self-Ag interactions (32). Our studies have suggested that self-Ag interactions played a role in the proliferation of self-specific CD8 T cells in vivo during LM infection (26).…”
Section: Self-ag Interactions Are Crucial For Maintaining the Memory supporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies had shown that the expansion of self-specific CD8 T cells in response to either IL-2 or IL-15 in vitro was independent of self-Ag interactions (32). Our studies have suggested that self-Ag interactions played a role in the proliferation of self-specific CD8 T cells in vivo during LM infection (26).…”
Section: Self-ag Interactions Are Crucial For Maintaining the Memory supporting
confidence: 63%
“…Previous reports have shown that self-specific CD8 T cells can proliferate and become activated in vitro in response to IL-2 or IL-15 (32). The expression of IL-2R␤ (CD122) in conjunction with common ␥ chain (CD132) is sufficient to confer lymphocytes with the ability to respond to both IL-2 and IL-15 (33,34).…”
Section: Il-15-activated Cells Provide Protection Against Lm Infectionmentioning
confidence: 99%
“…However, memory phenotype CD4 cells are also found in naive mice maintained under germfree conditions, suggesting that their development is not foreign Ag dependent (51). Because T cells from male anti-H-Y TCR-transgenic mice can develop extrathymically and display memory markers, it is possible that the development of memory phenotype CD8 T cells in naive mice is driven by the interaction of the ␣␤TCR with self-Ags and developed extrathymically (13,18,19). However, our finding that only a small percentage of CD8␣␤ cells develop in Txbm DKO mice compared with thymusintact bm chimeras suggests that most non-class Ia-selected CD8␣␤ cells are from the thymus-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2-activated CD8CD44 high cells are able to kill syngeneic tumor cells, suggesting that they may play a role in the surveillance of host cells that have been altered through infection or transformation (17). By analogy with H-Y Ag-specific TCR-transgenic mice, it has been suggested that the development of a significant portion of memory phenotype CD8 T cells in naive wild-type mice is driven by the interaction of ␣␤TCR with self-Ags and occurs extrathymically (13,18,19 (20). In the thymus of DKO mice, most mature single-positive CD8␣␤ T cells are CD44 low , similar to those in B6 mice (21).…”
Section: Thymus-dependent Memory Phenotype Cd8 T Cells Inmentioning
confidence: 99%
“…Another unusual feature of these CD8 lo T cells is that they proliferate in response to cytokines such as IL-2 and IL-15 in an antigen-independent manner. 9 However, the CD8 lo cells are similar to conventional memory T cells with regard to the ability to rapidly produce interferon ␥ (IFN-␥) upon TCR stimulation 10 and in respect to the killing of susceptible target cells without the need for additional reactivation with antigen. 11,12 CD8 ϩ T cells that develop via an extrathymic pathway and possessing similar functional characteristics are also found in normal (non-TCR transgenic) mice.…”
Section: Introductionmentioning
confidence: 99%